Pengembangan Alat Pemupuk Jagung Inovatif untuk Ketahanan Pangan yang Lebih Baik - Suwarni, Putri Endah; Sundari, Susanti; Khoirul, Samsul (Fakultas Teknik Universitas Tulang Bawang, 2024)
The development of an innovative corn fertilizer tool as an improvement on an existing concept that has been widely socialized in the farming community aims to design a fertilizer spreader tool that suits farmers' needs, with a simple technological concept, a working principle that is easy to operate and a product form that is easy to carry, and can be commercialized and is a development of previous concepts as the aim of the research carried out. Using the French method because it is considered easier to meet data needs. The design results obtained are an improvement on the research concept of previous researchers which improved the capacity where the old fertilizer tool was only able to accommodate approximately 2 Kg of fertilizer, with the new design it can accommodate 15 Kg of fertilizer, the tip of the lever is designed to be pointed so that the fertilizer enters the surface more easily. soil, while tool rods made from stainless steel can provide strength to the tool, they do not rust easily if they come into contact with water or fertilizer (chemicals) so they last a long time. Keywords: Corn Fertilizer Equipment, Capacity, Design, Innovative